Beach reprofiling to improve reproductive output at the world's largest remaining green turtle rookery: Raine Island, northern Great Barrier Reef. (1st January 2023) - Smithers, Scott G.; Dawson, John L.
Abstract: Raine Island is a low-lying reef island located on the outer edge of the northern Great Barrier Reef (nGBR). It is part of the Raine Island National Park (Scientific) and is managed to protect and conserve its exceptional natural, cultural, ecological and scientific values. High amongst these values is Raine Island's importance as the world's largest green turtle ( Chelonia mydas ) rookery. However, since at least the late 1990s the number of turtle hatchlings produced from nests on the island has significantly declined. The ramifications of reduced hatchling production at Raine Island for the nGBR green turtle population resulted in the establishment of the Raine Island Recovery Project (RIRP), a 5-year $AUS 7.95 million collaborative project involving government, industry and Traditional Owners. A primary aim of the RIRP is to restore viable turtle nesting habitat on Raine Island. Although reduced hatchling production and the potential demise of the nGBR green turtle population are very much an ecological concern, the key to understanding and addressing this management issue is largely geomorphological. Here we detail how the geomorphological attributes of Raine Island contributed to the drop in hatchling output, and outline how understanding and working with the geomorphology and coastal processes at Raine Island have contributed to the mitigation of that decline. In particular, geomorphological investigations established that the sand losses that have reduced the elevation of turtle nesting beaches were unlikely to be replenished by natural processes, and they informed strategic movements of beach sand to increase nesting habitat above tidal inundation which has boosted hatchling production by as much as 640, 000 over the past five years. Although this outcome is undoubtedly a success, the future remains challenging as anthropogenic climate change impacts progress. Graphical abstract: Image 1 Highlights: Raine Island is the world's largest remaining green turtle (Chelonia mydas) rookery. Declines in hatchling output due to drowned nests noted in recent decades. Low swales infilled with sand scraped from beach increased viable nest area by 35%. Geomorphological investigations underpinned the adaptive management works. Reprofiled areas are stable and have increased hatchling output from the island.